Studies of α-granule proteins in cultured human megakaryocytes - Veljkovic, Dragoslava Kika; Cramer, Elisabeth M.; Alimardani, Gulie; Fichelson, Serge; Massé, Jean-Marc; Hayward, Catherine P. M. (Thrombosis and Haemostasis, 2003)
α-Granule protein storage is important for producing platelets with normal haemostatic function. The low to undetectable levels of several megakaryocyte-synthesized α-granule proteins in normal plasma suggest megakaryocytes are important to sequester these proteins in vivo. α-Granule protein storage in vitrohas been studied using other cell types, with differences observed in how some proteins are processed compared to platelets. Human megakaryocytes, cultured from cord blood CD34+cells and grown in serum-free media containing thrombopoietin, were investigated to determine if they could be used as a model for studying normal α-granule protein processing and storage. ELISA indicated that cultured megakaryocytes contained the α-granule proteins multimerin, von Willebrand factor, thrombospondin-1, β-thromboglobulin and platelet factor 4, but no detectable fibrinogen and factor V. A significant proportion of the α-granule protein in megakaryocyte cultures was contained within the cells (averages: 41 – 71 %), consistent with storage. Detailed analyses of multimerin and von Willebrand factor confirmed that α-granule proteins were processed to mature forms and were predominantly located in the α-granules of cultured megakaryocytes. Thrombopoietin-stimulated cultured megakaryocytes provide a useful model for studying α-granule protein processing and storage.
Keywords: Megakaryocytes; platelets; α-granules; protein processing